The level of adoption of green supply chain management and green innovation in Malaysian manufacturing industries - Abu Seman, Noor Aslinda; Zakuan, Norhayati; Rashid, Umi Kartini; Nasuredin, Juzaimi; Ahmad, Nurazwa (IJR, 2018)
Recently, corporate environmental practice such as Green Supply Chain Management (GSCM) and green innovation appears as a novel organized environmental practice for manufacturing companies to handle the increasing environmental issues. The aim of this paper is to assess the level of adoption of GSCM and green innovation practices. A total of 123 responses from Malaysian manufacturing companies were collected from mail questionnaire. The results showed Malaysian manufacturing companies are in trial adoption stage for both GSCM practices and green innovation. Internal environmental management practice of GSCM practices are relatively high adopted in Malaysian manufacturing organisation. Meanwhile, most of all green innovation practices are heavily implemented in Malaysian manufacturing companies. This paper empirically attempts to provide understanding and new insights for sustainability management area where GSCM and green innovation practices are important to improve organisational environmental performance, which can directly offer great benefits for both researchers and practitioners.